Global governance in a world of change - Barnett, Michael N., 1960-; Raustiala, Kal; Pevehouse, Jon C.w (Cambridge University Press, 2022)
Global governance has come under increasing pressure since the end of the Cold War. In some issue areas, these pressures have led to significant changes in the architecture of governance institutions. In others, institutions have resisted pressures for change. This volume explores what accounts for this divergence in architecture by identifying three modes of governance: hierarchies, networks, and markets. The authors apply these ideal types to different issue areas in order to assess how global governance has changed and why. In most issue areas, hierarchical modes of governance, established after World War II, have given way to alternative forms of organization focused on market or network-based architectures. Each chapter explores whether these changes are likely to lead to more or less effective global governance across a wide range of issue areas. This provides a novel and coherent theoretical framework for analysing change in global governance.